Concurrent Quad-band Low Noise Amplifier (QB-LNA) using Multisection Impedance Transformer - Teguh Firmansyah; Anggoro Suryo Pramudyo; Siswo Wardoyo; Romi Wiryadinata; Alimuddin Alimuddin (International Journal of Electrical and Computer Engineering (IJECE), 2017)
A quad-band low noise amplifier (QB-LNA) based on multisection impedance transformer designed and evaluated in this research. As a novelty, a multisection impedance transformer was used to produce QB-LNA. A multisection impedance transformer is used as input and output impedance matching because it has higher stability, large Q factor, and low noise than lumpedcomponent.The QB-LNA was designed on FR4 microstrip substrate with er= 4.4, thickness h=0.8 mm, and tan d= 0.026. The proposed QB-LNA was designed and analyzed by Advanced Design System (ADS).The simulation has shown that QB-LNA achieves gain (S21) of 22.91 dB, 16.5 dB,  11.18 dB, and 7.25 dB at 0.92 GHz, 1.84 GHz, 2.61 GHz, and 3.54 GHz, respectively.The QB-LNA obtainreturn loss (S11) of -21.28 dB, -31.87 dB,  -28.08 dB, and -30.85 dB at 0.92 GHz, 1.84 GHz, 2.61 GHz, and 3.54 GHz, respectively. It also achieves a noise figure (nf) of 2.35 dB, 2.13 dB, 2.56 dB, and 3.55 dB at 0.92 GHz, 1.84 GHz, 2.61 GHz, and 3.54 GHz, respectively. This research also has shown that the figure of merit (FoM) of the proposed QB-LNA is higher than that of another multiband LNA.